ANALISA PROFIL BANDWIDTH JARINGAN COPPER, FIBER OPTIK DAN MIGRASI SERTA LOSS LINK BUDGET DI PT TELKOM KEDIRI: ANALISA PROFIL BANDWIDTH JARINGAN COPPER, FIBER OPTIK DAN MIGRASI SERTA LOSS LINK BUDGET DI PT TELKOM KEDIRI - MUSTOFA, INDRA HADI; Sarbini, Riska Nurtantyo; Kurniadi, Harso (Generation Journal, 2019)
In the case of indihome 3P services, the copper network is not able to send internet data that has a maximum of </ = 3 Mbps, therefore it is migrated to an optical fiber network that sends bandwidth up to> 100 Mbps. The average copper upload network bandwidth is 0.62 and download is 3.28 Mbps, and the fiber optik network for uploading 2.57 Mbps and uploads is 11.62 Mbps, and upload migration is 7.01Mbps and downloading 10.73 Mbps Attenuation of copper upload networks is 16.82 dBm and download is 33.77 dBm and optical fiber network or upload attenuation migration is 2.44dBm and download is -20.34 dBm. Fiber optik cable in data transmission via 1310 nm upload wave, 1490 nm download, 1550 nm streaming with loss link budget </ = -28 dBm. Keywords: Copper, Optical Fiber, Migration, Bandwidth, Loss Link Budget.